Biodiversity of macroalgae in Blue Lagoon, the Straits of Malacca, Malaysia and some aspects of changes in species composition - I. Asmida,; A.B. Noor Akmal,; I. Ahmad,; M. Sarah Diyana, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This research was conducted to study the biodiversity status of marine macroalgae (seaweeds) in Blue Lagoon, Port Dickson and assess the changes in species composition in the area. The sampling site is located in the west coast of Peninsular Malaysia, which has been regarded as one of the Malaysia’s popular beach resort destinations. This tourist spot has seen major physical changes over the last few decades. Despite habitat disturbance, our study recorded 44 species of macroalgae with Sargassum asperifolium noted as a new record for this area. Brown seaweeds (Phaeophyta) and green seaweeds (Chlorophyta) dominated the sampling areas with each division recorded 19 and 16 species, respectively. Change to species composition was evident for the common genus Sargassum (Sargassaceae, Fucales). Chlorophyta was mostly found in the upper intertidal to subtidal zones while Phaeophyta proliferated in the mid-tidal areas. The red seaweeds (Rhodophyta) were distributed and grew better in lower light intensity in the subtidal zone. This study will contribute to the seaweed database of Malaysia for future reference and this may help in the conservation of seaweeds.